Pendampingan UMKM Naik Kelas melalui Legalitas Usaha dan Strategi Pemasaran di Desa Sukajaya Kecamatan Pulau Besar Kabupaten Bangka Selatan - Muhamad Aziz Zulkifli; Siti Napisah; Bagas Olanda; Andini Fahyuni (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2025)
his community service activity was carried out in Sukajaya Village, Pulau Besar District, Bangka Selatan Regency on August 15, 2025, aiming to enhance the capacity of Micro, Small, and Medium Enterprises (MSMEs) to level up through strengthening business legality and marketing strategies. The main problems faced by local MSMEs are the lack of understanding regarding the importance of Business Identification Numbers (NIB), limited awareness of trademark protection, and insufficient knowledge of modern marketing strategies. The activity was implemented using a participatory approach through counseling, group discussions, and hands-on practices, including NIB registration, introduction to trademark protection procedures, and digital marketing training. The results show an increased understanding and awareness among MSME actors regarding the importance of business legality for accessing financing and cooperation, better legal awareness of trademark protection as a product identity, and basic skills in utilizing social media and digital platforms as marketing tools. These outcomes demonstrate that the activity significantly contributes to strengthening MSME capacity in Sukajaya Village to become more competitive and contribute to local economic development.